In-situ polymerization of isotactic polypropylene-nanographite nanocomposites. (2nd December 2015) - Cromer, Brian M.; Scheel, Saskia; Luinstra, Gerrit A.; Coughlin, E. Bryan; Lesser, Alan J.
Abstract: Isotactic Polypropylene-Exfoliated Graphene Nanoplatelet (iPP-xGnP™) nanocomposites were prepared through an in-situ polymerization technique and compared to analogous composites prepared by melt compounding. In-situ preparation of iPP-xGnP nanocomposites was accomplished via single site metallocene polymerization of propylene within a toluene dispersion of xGnP nanoparticles. The in-situ prepared nanocomposites were compared to analogous nanocomposites prepared by melt compounding of commercial Ziegler–Natta iPP with xGnP. Optical microscopy showed the in-situ prepared nanocomposites demonstrated poorer xGnP dispersion compared to composites prepared by melt compounding. All xGnP-reinforced nanocomposites demonstrated increased crystallization temperature, as well as increases in mechanical strength and modulus, relative to neat iPP. However, the non-linear mechanical properties were found to be influenced by the both the preparation method and nanoparticle loading. Nanocomposites prepared by in-situ polymerization generally demonstrated superior ductility and fracture toughness compared to composites prepared by melt compounding. The results are discussed with regard to the preparation technique and xGnP loading. Graphical abstract: Highlights: Polypropylene-Nanographite (iPP-GnP) composites were made via in-situ polymerization. Analogous iPP-GnP composites were also prepared by melt compounding for comparison. In-situ prepared composites demonstrated the poorest nanoparticle dispersion. All iPP-GnP composites demonstrated increased mechanical strength and modulus. Relations between mechanical properties and the preparation method are discussed.